New Product Search Over Time: Past Ideas in Their Prime? - Katila, Riitta (Academy of Management Journal, 2002)
This paper investigates how the age of the knowledge that firms search affects how innovative they are. Two seemingly contradictory propositions are examined: (1) old knowledge hurts by making innovation activities obsolete, and, (2) old knowledge helps because it is more reliable and legitimate, thereby promoting innovation. Results based on longitudinal data on 131 robotics firms reconcile the contradictory propositions: while old intra-industry knowledge hurts, old extra-industry knowledge promotes innovation.